Sonophotocatalytic Dye Degradation Using rGO-BiVO4 Composites - Kumar M.; Ansari M.N.M.; Boukhris I.; Al-Buriahi M.S.; Alrowaili Z.A.; Alfryyan N.; Thomas P.; Vaish R. (John Wiley and Sons Inc, 2023)
Reduced graphene oxide (rGO)/bismuth vanadate BiVO4 composites are fabricated with varied rGO amounts (0, 1, 2, and 3wt%) through the synergetic effects of ultrasonication, photoinduced reduction, and hydrothermal methods, and the materials are tested as tools for sonophotocatalytic methylene blue (MB) dye degradation. The effect of rGO content on the sonophotocatalytic dye degradation capabilities of the composites are explored. Characterization of the proposed materials is done through transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier transformation infrared spectroscopy as well as scanning electron microscopy. The coexistence of BiVO4 and rGO is confirmed using Raman spectroscopy and XRD. TEM confirms the existence of interfaces between rGO and BiVO4 and XPS affirms the existence of varied elemental oxidation states. In order to investigate the charge carriers transportation, time-dependent photocurrent responses of BiVO4 and 2wt%- rGO/BiVO4 are done under visible light irradiation. The sonophotocatalytic MB dye degradation in an aqueous medium displays promising enhancement with rGO doping in rGO/BiVO4 composite. The 2wt%- rGO/BiVO4 sample exhibits ?52% MB dye degradation efficiency as compared to pure BiVO4 (?25%) in 180min of the sonophotocatalysis experiment. Phytotoxicity analysis through germination index is done using vigna radiata seeds. 2022 The Authors. Global Challenges published by Wiley-VCH GmbH.